2004
DOI: 10.1590/s1413-86702004000400002
|View full text |Cite
|
Sign up to set email alerts
|

Audit of antibiotic use in a Brazilian University Hospital

Abstract: A cohort study was carried out at the Marilia Medical School Hospital. In the first phase the pattern of antibiotic use was evaluated. Antibiotics were prescribed for 55.4% of the patients; antibiotic combinations were used in 43%. Therapeutic use of antibiotics was considered inadequate in 27%. Respiratory and skin infections were the most frequently diagnosed. In up to 31% of the cases the treatment of respiratory infections was considered inadequate. The surgical use of antibiotic prophylaxis was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
3
9
2
3
Order By: Relevance
“…Inappropriate timing may result in low plasma concentration of the antimicrobial agent at the time of incision and throughout the procedure [13], contributing to higher infection rates [14]. In contrast to other studies [8,15], our results indicated that 49% of physicians administered the SAP at the time of anesthesia induction. This is considered the correct timing according to ASHP guidelines for most procedures, since this ensures adequate antibiotic concentrations in the targeted tissues during the period of potential contamination [7].…”
Section: Discussioncontrasting
confidence: 73%
“…Inappropriate timing may result in low plasma concentration of the antimicrobial agent at the time of incision and throughout the procedure [13], contributing to higher infection rates [14]. In contrast to other studies [8,15], our results indicated that 49% of physicians administered the SAP at the time of anesthesia induction. This is considered the correct timing according to ASHP guidelines for most procedures, since this ensures adequate antibiotic concentrations in the targeted tissues during the period of potential contamination [7].…”
Section: Discussioncontrasting
confidence: 73%
“…The misuse of antibiotics contributes to this dilemma [14]. In our study, the 25% nonindicated antibiotic prescriptions was within the range of 15.5–72% reported in other studies [15,16,17,18]. The unwarranted prescription of antibiotics among physicians could be due to inaccurate diagnosis, imprecise recognition of conditions that can be treated with antibiotics, and concerns of a poor clinical outcome when antibiotics are not given [19].…”
Section: Discussionsupporting
confidence: 56%
“…However; for other clean neck surgeries and hernia repair it is not recommended due to the low incidence of wound infection [15]. In Brazil Fonseca and Contemnor reported that 26% of patients were unnecessarily given antibiotics for surgical prophylaxis [16].…”
Section: Discussionmentioning
confidence: 99%